2019
DOI: 10.1371/journal.pone.0208084
|View full text |Cite
|
Sign up to set email alerts
|

Role of freshwater floodplain-tidal slough complex in the persistence of the endangered delta smelt

Abstract: Seasonal floodplain wetland is one of the most variable and diverse habitats found in coastal ecosystems, yet it is also one of the most highly altered by humans. The Yolo Bypass, the primary floodplain of the Sacramento River in California’s Central Valley, USA, has been shown to provide various benefits to native fishes when inundated. However, the Yolo Bypass exists as a tidal dead-end slough during dry periods and its value to native fishes has been less studied in this state. During the recent drought (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…due to reduced predation risk or higher prey availability) in turbid conditions may help facilitate growth compensation during periods of thermal stress, as has been shown for other temperate fishes (Lusardi et al 2020). If so, this may explain, in part, the ability of some freshwater resident delta smelt to survive otherwise thermally stressful conditions during warm summer conditions (Hobbs et al 2019, Mahardja et al 2019.…”
Section: Extrinsic Effects: Claritymentioning
confidence: 89%
“…due to reduced predation risk or higher prey availability) in turbid conditions may help facilitate growth compensation during periods of thermal stress, as has been shown for other temperate fishes (Lusardi et al 2020). If so, this may explain, in part, the ability of some freshwater resident delta smelt to survive otherwise thermally stressful conditions during warm summer conditions (Hobbs et al 2019, Mahardja et al 2019.…”
Section: Extrinsic Effects: Claritymentioning
confidence: 89%
“…These long-term monitoring studies have documented the persistence of Delta Smelt in the tidal freshwaters of the lower Sacramento River near the town of Rio Vista year-round, but due to their close proximity to brackish water, it was not acknowledged that Delta Smelt could complete their life cycle in freshwater in the wild 26 . Since 2002, additional surveys conducted in the North Delta have documented year-round presence and, at times, high abundance of Delta Smelt, suggesting freshwater resident fish may be important to the population 31,32,52,53 . Our otolith 87 Sr/ 86 Sr chronologies confirmed the existence of a freshwater resident life history comprising 12% of the adult population in this abundant year-class.…”
Section: Discussionmentioning
confidence: 99%
“…Two of our semi-anadromous clusters had natal 87 Sr/ 86 Sr consistent with hatching in the North Delta and their age-at-dispersal into brackish water was much older, suggesting fish hatched in this region may have found it difficult to disperse downstream into the estuary. Recently, studies have found evidence of degraded health in Delta Smelt found in the North Delta during summer months, exhibiting poor feeding, somatic condition and growth rates in addition to histological lesions consistent with contaminant exposure 53,59–61 . Collectively, these studies suggest survival may be impaired for fish in the North Delta and conditions in this region of the estuary may play a large role in the decline of Delta Smelt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While food web resources have declined throughout much of the upper estuary, the Cache Slough Complex (CSC) in the north Delta region of the upper estuary (Figure 1) frequently has relatively higher levels of phytoplankton than other areas in the estuary (Downing et al 2016;Lehman et al 2010;Lehman et al 2008). The region is notable because it retains some of the more complex tidal slough channels characteristic of the historical Delta, and is connected to the Yolo Bypass, a large floodplain (Sommer et al 2001;Whipple et al 2012) with higher plankton densities (Mahardja et al 2019). The region therefore contains a much larger network of shallow habitat and long-residencetime channels, which are hypothesized to promote the development of planktonic food https://doi.org/10.15447/sfews.2021v19iss3art3 resources (Lucas et al 2009).…”
Section: Introductionmentioning
confidence: 99%